Is there evidence of inefficiency in the Football Betting Market? - Viraj Thakor, V.T (2016)
This dissertation investigates the existence of both weak form and semi-strong form efficiency in the football betting market over the last 8 seasons (2008/2009 to 2015/2016), for the English Premier League, the German Bundesliga and the Spanish La Liga.